2017
DOI: 10.1111/jbi.13049
|View full text |Cite
|
Sign up to set email alerts
|

The historical connections between the Amazon and the Atlantic Forest revisited

Abstract: Aim: To assess ancient biotic connections between the Amazon Forest (AmF) and the Atlantic Forest (AtF) based on environmental niche modelling (ENM), palaeobiological, and molecular evidence; to test Por (1992)'s hypothesis of the south-eastern -north-western (SE-NW) route as the most important route in terms of frequency and duration; to evaluate past climatic conditions associated with the routes.Location: South America. Methods:We generated random points in climate space of AmF and AtF and identified two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
138
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 66 publications
17
138
0
4
Order By: Relevance
“…We found signs of population expansion of P. m. melanonota within the Atlantic Forest, which is congruent with previous reports for other forest specialists that inhabit this region (e.g. Cabanne, D'Horta, Sari, Santos, & Miyaki, ; Harvey & Brumfield, ; Lavinia et al, ; Trujillo‐Arias et al, ), and is probably the consequence of Pleistocene climatic oscillations that altered the spatial coverage of the Atlantic Forest (Ledo & Colli, ; Ribas, Maldonado et al, ; Sobral‐Souza, Lima‐Ribeiro, & Solferini, ). By contrast, our results suggest population stability within the Andes region, in agreement with what has been reported for other Andean and western Amazonian taxa and indicating that forests from the west side of the continent might have been more stable than their eastern counterparts (Cheng et al, ; Ribas, Aleixo et al, ; Sobral‐Souza et al, ; Trujillo‐Arias et al, ), with the exception of the high Andes, where Pleistocene climatic cycles had a more direct and profound effect (Weir, ).…”
Section: Discussionsupporting
confidence: 92%
“…We found signs of population expansion of P. m. melanonota within the Atlantic Forest, which is congruent with previous reports for other forest specialists that inhabit this region (e.g. Cabanne, D'Horta, Sari, Santos, & Miyaki, ; Harvey & Brumfield, ; Lavinia et al, ; Trujillo‐Arias et al, ), and is probably the consequence of Pleistocene climatic oscillations that altered the spatial coverage of the Atlantic Forest (Ledo & Colli, ; Ribas, Maldonado et al, ; Sobral‐Souza, Lima‐Ribeiro, & Solferini, ). By contrast, our results suggest population stability within the Andes region, in agreement with what has been reported for other Andean and western Amazonian taxa and indicating that forests from the west side of the continent might have been more stable than their eastern counterparts (Cheng et al, ; Ribas, Aleixo et al, ; Sobral‐Souza et al, ; Trujillo‐Arias et al, ), with the exception of the high Andes, where Pleistocene climatic cycles had a more direct and profound effect (Weir, ).…”
Section: Discussionsupporting
confidence: 92%
“…Amazonia was recovered as the main source of parasite lineage dispersal into the Caatinga (the driest region) and Andean‐Patagonian Forest as well, despite a lack of current connection between Amazonia and these two regions. A high level of Plasmodium dispersal from Amazonia into the Atlantic Rain Forest was observed, which concurs with several studies on vertebrates that suggest periodic contact between these biomes since the Miocene (Costa, ; Batalha‐Filho, Fjeldså, Fabre, & Miyaki, ; Ledo & Colli, ). The high level of Plasmodium lineage dispersal from the Atlantic Rain Forest to the Peruvian Andes is remarkable considering the geographical distance and isolation between these two regions.…”
Section: Discussionsupporting
confidence: 89%
“…Hypsiboas lundii mostly occurs in gallery forests, the most mesic habitat of the Cerrado savanna, and its response might be only representative of organisms in this environment. Ledo and Colli (), for example, showed that LGM favoured the expansion of forest habitats allowing a connection between the Atlantic Forest and the Amazon through a southeast‐northwest route. The gallery forests in the Cerrado might have followed this pattern, given that our LGM model was also more widespread towards the western Cerrado.…”
Section: Discussionmentioning
confidence: 99%